Sex differences in arterial stiffness and ventricular-arterial interactions - Coutinho, Thais; Borlaug, Barry A; Pellikka, Patricia A; Turner, Stephen T; Kullo, Iftikhar J (Journal of the American College of Cardiology, 2013)
This study sought to assess sex differences in ventricular-arterial interactions. Heart failure with preserved ejection fraction is more prevalent in women than in men, but the basis for this difference remains unclear. Echocardiography and arterial tonometry were performed to quantify arterial and ventricular stiffening and interaction in 461 participants without heart failure (189 men, age 67 ± 9 years; 272 women, age 65 ± 10 years). Aortic characteristic impedance (Z(c)), total arterial compliance (pulsatile load), and systemic vascular resistance index (steady load) were compared between men and women, and sex-specific multivariable regression analyses were performed to assess associations of these arterial parameters with diastolic dysfunction and ventricular-arterial coupling (effective arterial elastance/left ventricular end-systolic elastance [Ea/Ees]) after adjustment for potential confounders. Z(c) was higher and total arterial compliance was lower in women, whereas systemic vascular resistance index was similar between sexes. In women but not men, higher log Z(c) was associated with mitral inflow E/A ratio (β ± SE: -0.17 ± 0.07), diastolic dysfunction (odds ratio: 7.8; 95% confidence interval: 2.0 to 30.2) and Ea/Ees (β ± SE: 0.13 ± 0.04) (p ≤ 0.01 for all). Similarly, total arterial compliance was associated with E/A ratio (β ± SE: 0.12 ± 0.04), diastolic dysfunction (odds ratio: 0.33; 95% confidence interval: 0.12 to 0.89), and Ea/Ees (β ± SE: -0.09 ± 0.03) in women only (p ≤ 0.03 for all). Systemic vascular resistance index was not associated with diastolic dysfunction or Ea/Ees. Proximal aortic stiffness (Z(c)) is greater in women than men, and women may be more susceptible to the deleterious effects of greater pulsatile and early arterial load on diastolic function and ventricular-arterial interaction. This may contribute to the greater risk of heart failure with preserved ejection fraction in women.